2015
DOI: 10.11591/ijece.v5i3.pp464-476
|View full text |Cite
|
Sign up to set email alerts
|

HybridConcatenated Coding Scheme for MIMO Systems

Abstract: <!--?xml:namespace prefix = "o" ns = "urn:schemas-microsoft-com:office:office" /-->Abstract: Inthis paper, two hybrid concatenated super-orthogonal space-time trellis codes(SOSTTC) applying iterative decoding are proposed for flat fading channels. Theencoding operation is based on the concatenation of convolutional codes,interleaving and super-orthogonal space-time trellis codes. The firstconcatenated scheme consists of a serial concatenation of a parallelconcatenated convolutional code with a SOSTTC whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Depending on the availability of channel state information (CSI) on the relay nodes, several strategies for wireless sensor networks have been recently suggested to generalize and improve cooperative diversity strategies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Some strategies are based on unrealistic assumptions such as perfect CSI available at all nodes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the availability of channel state information (CSI) on the relay nodes, several strategies for wireless sensor networks have been recently suggested to generalize and improve cooperative diversity strategies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Some strategies are based on unrealistic assumptions such as perfect CSI available at all nodes [15].…”
Section: Introductionmentioning
confidence: 99%
“…of carriers as well as no. of operators will increase on same roof top, this power will increase several times [10]. Experimentally, it has been observed that radiation density will be much lower away from the main beam direction.…”
Section: Power Density Of Bts For Different Source Distancementioning
confidence: 97%
“…In this paper, hybrid concatenated super-orthogonal space-time trellis codes (SOSTTC) applying iterative translating are proposed for level fading channels. The proposed topologies are appeared to perform superior to anything existing connected plans with aconstituent code of convolutional and space-time codes in writing [14]. This paper explains the concept of correlation among the carrier signals and sub channels.…”
Section: Introductionmentioning
confidence: 94%